Synthesis and Characterization of Pine Needles Reinforced RF Matrix Based Biocomposites - A. S. Singha; Vijay Kumar Thakur (E-Journal of Chemistry)
Synthesis and characterization of pine needles reinforced thermosetting resin (Resorcinol-Formaldehyde) which is most suitable as composite matrix has been reported. The polycondensation reaction between resorcinol and formaldehyde (RF) in different molar ratios has been applied to the synthesis of RF polymer matrix. A thermosetting resin based composite, containing approximately 10, 20, 30 and 40% of natural fiber by weight, has been obtained by adding pine needles to the Resorcinol-Formaldehyde (RF) resin. The mechanical properties of randomly oriented intimately mixed particle reinforced (Pine needles) composites were determined. Effect of fiber loading in terms of weight % on mechanical properties such as tensile, compressive, and flexural and wear properties have also been evaluated. The reinforcing of the resin with Pine needles was accomplished in particle size of 200 micron by employing optimized resin. Present work reveals that mechanical properties of the RF resin increases to extensive extent when reinforced with Pine needles. Thermal (TGA/DTA) and morphological studies (SEM) of the resin, fiber and polymer composites thus synthesized have also been carried out.